Detection of rtxA Gene as a Biomarker of Seafood-Borne Pathogen Vibrio cholerae using In Silico PCR Assay - Stalis Norma Ethica; Nur Hidayati; Hayatun Fuad; Chaerul Arham; Rivana Ariyadi; Ellyka Purwaningrum; Kazi Mohammad Zillur Rahman (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2020)
Seafood-borne outbreaks caused by Vibrio cholerae have led to the increased need for food safety risk assessment of marine products. An in silico investigation about the potential of virulence gene of V. cholerae, rtxA, as a DNA biomarker of the toxigenic bacterium has been carried out. The aim of this study was to use the bacterial DNA biomarker sequence as a tool to facilitate early rapid detection of cholera infection. Five specific pairs of primers were designed from the rtxA open reading frame DNA of V. cholerae O1 biovar El Tor str. N16961 genomic DNA using Primer3Plus. Next, in silico Polymerase Chain Reaction (PCR) assay was carried out using the newly designed primers and 25 genomic DNA of vibrio spp. retrieved from the in silico database. One of the five designed pairs of primers, RtxAOF-RtxAOR: ‘5-CGCAAAACAGTTTCAGCCGA-3’ and 5’-AGGTTGGTCTTTTGTGGCCA-3’, could result in single DNA amplicon sized 518 bp only from V. cholerae species. No amplicon bands were produced from 17 other vibrio genomes studied using similar RtxAF-RtxAR primers. A further check showed that the amplicon was indeed part of the rtxA gene of V. cholerae. Based on this in silico study, rtxA gene appeared to be a DNA biomarker of V. cholerae, which is potential to facilitate rapid diagnosis of the virulence bacterium using in silico PCR assay.